In search of a rational criminal policy: criteria of legislative rationality in the EU Criminal Law-Making process - Corral Maraver, Noelia (My University, 2017)
The past and current criminal policy in the EU presents, like it does in many Member States, serious shortcomings, such as the extension of the Law and Order approach, expansion of Criminal Law, legislative improvisation, the continuous over-criminalisation and raising of penalties, subordination of substantive Criminal Law to police and judicial cooperation and technocratisation and petrification of criminal standards. For a long time, the continuous focus only on competence problems and effectiveness criteria –to strengthen the principle of mutual trust and improve judicial and police cooperation in criminal matters- did not contributed greatly to the formation of a more rational substantive Criminal Law. To sum up, all these shortcomings often end up causing an over-criminalisation and homogenisation of the diverse national criminal legal systems in terms of greater punitive rigor, increasingly infringing fundamental principles. Criminal lawyers and also other academic disciplines must address these problems by setting up mechanisms that could help to reduce or eliminate the current EU criminal policy rationality defects. Taking into account that many of the above-mentioned shortcomings of EU criminal policy could reasonably result from a lack of rationality in the EU criminal decision-making process, paying more attention to science of law-making and legislative procedures within the European Union would certainly be a good start. In the last few years we have seen an increase of interest in the study of Criminal Law-making processes as a way of improving law quality. There have been efforts to contribute to a more rational approach from different perspectives. Sometimes appealing to widely accepted concepts, such as legal interest, or important principia (proportionality, legality, subsidiarity, ultima ratio…). Despite the large importance of such works, none of them have the potentiality to support all the rationality contents needed for a European Criminal Law that provides all possible guarantees and complies with fundamental principles and legal safeguards. For these reasons I argue in favour to make a new and more comprehensive approach, focusing in the stage of creation of the laws. The proposal is to adopt a law rationality model –based in the previous works of Prof. Atienza and Prof. Díez Ripollés- that could act as guideline for EU law-makers. The law rationality model proposed aims to be an ambitious instrument to provide rationality criteria for the creation of law. It has 5 levels (ethic rationality, teleological rationality, pragmatic rationality, systematic rationality and linguistic rationality). Thus, a criminal provision can be said to be irrational when it does not comply with any of these levels of rationality. It is a great challenge but also would be of interest to adapt this theoretic model to the European stage. In my view it would be able to contribute to the creation of a more rational and guarantee-based EU criminal policy and to overcome the current fragmentary approach to substantive Criminal Law in the EU.
Keywords: Derecho penal - Legislación; Law-Making process; European Criminal Law; Rationality